Movement of Domestic Tourist in Malaysia in 2010 = Pergerakan Pelancong Domestik di Malaysia Tahun 2010 - Azizul, Ahmad; Nur Afiqah, Ariffin; Yaniza Shaira, Zakaria; Ardiansyah, Ardiansyah; Norizawati, Mohd Ayob; Lindah Roziani, Jamru; Nur Rafidah Asyikin, Idris; Tarmiji, Masron ((UPSI Press), Universiti Pendidikan Sultan Idris., 2024)
Malaysia is a one of the countries that was awarded with various natural attractions. The variety of race also built colorful culture that always offered variety prospects to tourists. Tourism industry in this country has gained attention as one of the main sectors in generating income. Therefore, many strategies have been planned and implemented to promote Malaysia as one of the main tourist hubs in the world. Tourism involving people movement through time and space, tourist experience in some locations is different and their consumption influenced by the pattern of movement. Pattern and trend of tourist movement influenced by various factors, and it was individualistic whether for domestic tourist or international tourist. Understand how tourist move through time and space is important to be implemented for infrastructure and transportation development, product development, destination and new attraction planning and it also important for management studies impact to social, environment and culture that caused by tourism sector. Using domestic tourist data from 2010 in Malaysia, the objective of this paper is to identify the pattern and trends of domestic tourist movement using GIS applications. In addition, this paper also aims to examine the significance of the destination choices made​​ by the tourists.